To Play Many Parts: Reading Between the Lines of Charlotte Salomon/CS’s Leben? oder Theater? Nicholas Chare in conversation with Griselda Pollock - Chare, Nicholas (RACAR : Revue d'art canadienne / Canadian Art Review, 2018)
This conversation with Griselda Pollock, Professor of the Social and Critical Histories of Art in the School of Fine Art, History of Art and Cultural Studies at the University of Leeds, UK, focuses on her most recent book, Charlotte Salomon and the Theatre of Memory (New Haven and London : Yale University Press, 2018). The latter provides new readings of Leben ? oder Theater ? (Life ? or Theater ?), the artistic project of the German Jewish artist Charlotte Salomon (1917–1943), who painted as CS — the cipher the artist purposely used to disguise both her gender and her ethnicity — thus challenging previous interpretations that treat this remarkable intermedial work as straightforwardly autobiographical.